Gender Differences in Academic Performance of Financial Accounting Students in Selected Senior High Schools in the Central Region of Ghana - Sam, Leticia (Advances in Social Sciences Research Journal, 2016)
ABSTRACT The study examined gender differences in the academic performance of Financial Accounting students in selected senior high schools in the Central Region of Ghana. Descriptive survey design was employed for the study, 331 students and 137 teachers of Financial Accounting were surveyed. The study found that male students studying Financial Accounting perform better than female students. The study also revealed that there are gender differences in students’ academic performance in Financial Accounting. Accordingly, it is recommended that accounting teachers should put their students into groups and assign them group task. This grouping should be done in such a way that group will consist of both male and female Financial Accounting students with different performance levels so that the female students who do not actually perform well will find the ideas of their male colleagues useful. Moreover, teachers should try to make Financial Accounting appealing to students by making it practical and relevant to the lives of the students as much as possible.